2014
DOI: 10.1186/1471-2393-14-162
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social support around pregnancy on postpartum depression among Canadian teen mothers and adult mothers in the maternity experiences survey

Abstract: BackgroundPostpartum depression (PPD) is a mood disorder that affects 10–20 percent of women, and can begin any time during first year after delivery lasting for months. Social support may decrease risk of depression during pregnancy for women. However, literature shows that the amount of social support received during and after pregnancy is different for teen mothers and adult mothers. This study examined the effects of social support received during and after pregnancy on PPD among Canadian women and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
5
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(133 citation statements)
references
References 31 publications
(54 reference statements)
8
106
5
14
Order By: Relevance
“…In summary, the following patients beliefs constitute the risk factors for postpartum blues: 'I need support (need), but I will not receive as much as I need (perceived available), especially specific instructions (instrumental), and I will not admit to being in a bad mood (buffering-protective scale)' . The role of social support has been confirmed by numerous studies [16,20].…”
Section: Discussionmentioning
confidence: 73%
“…In summary, the following patients beliefs constitute the risk factors for postpartum blues: 'I need support (need), but I will not receive as much as I need (perceived available), especially specific instructions (instrumental), and I will not admit to being in a bad mood (buffering-protective scale)' . The role of social support has been confirmed by numerous studies [16,20].…”
Section: Discussionmentioning
confidence: 73%
“…25,26 However, a recently published study examining the effects of social support on Canadian women during and after pregnancy found that teenage mothers received more social support from the family during pregnancy than adult mothers. 27 The authors argue that because teenagers present more difficulties to connect with their peers, the family may end up providing more support. Despite the weak association, we can consider that older mothers have more experience in life, so that their family would not provide the same amount of support demanded by younger women.…”
Section: Discussionmentioning
confidence: 99%
“…Women with an EPDS score of 9 or over were 1.88 times the likelihood of experiencing any injury (95 % CI 1.49-2.37) in the bivariate model, which remained significant even after adjusting for potential confounders (OR 1.59, 95 % CI 1.24-2.04). Regarding EPDS association The number of injuries exceeded the number of infants due to multiple answers allowed a Other injuries (n): fall from other furniture or heights (71); bruises (41); stepped on by siblings (14); bitten by siblings (7); cut by nail-scissors (6); caught fingers in other objects (3); scratches (3); nearsuffocation (3); cut wounds (2); insect bites (2); low temperature burn (2); nasal bleeding (1); oral injury due to sibling inserting toothbrush too deeply into infant's mouth (1), pulled elbow (1); bleeding from infant's nipple (1); hair caught in something (1); no injuries (15) with specific unintentional injury, women with an EPDS score of 9 or more were 1.41 times the likelihood of experiencing a fall (95 % CI 1.02-1.95). After adjusting for potential covariates, near-drowning was not significant (OR 1.49, 95 % CI 0.74-3.00).…”
Section: Resultsmentioning
confidence: 99%